Zázemí hradiště Mikulčice-Valy v 9. století - Hladík, Marek; Mazuch, Marian; Poláček, Lumír (2020)
The book provides a brief overview of the most important archaeological sites of the 9th century in the immediate vicinity of the Slavic fortified settlement in Mikulčice. Mikulčice “Valy” – the leading center of Great Moravia – has been researched by the staff of the Institute of Archaeology of the Academy of Sciences, Brno, since 1954. Archaeological research of unfortified settlements and burial grounds provides information for understanding the whole Great Moravian society, especially its socio-economic structure. In the book, the reader will gradually get acquainted with the best-explored Great Moravian settlements and burial grounds in the vicinity of Mikulčice, within the alphabetically arranged cadastral areas on the Czech and Slovak side of the Morava River. Even before that – in the introduction to the book – attention is focused on the historical landscape and the development of research from its beginnings in the last century to the application of modern archaeological methods in the so-called landscape and spatial archaeology. At the end of the book, the reader will find interpretive models, which can be used to clearly explain the main patterns of economic and social relations of the center of Mikulčice with its economic hinterland